Psicologia crítica africana e descolonização da vida na prática da capoeira Angola - Nogueira, Simone Gibran (2013)
This research had two main objectives: the first one aimed to demonstrate and defend the coherency of using theoretical, epistemological and methodological perspectives culturally consistent with the African worldview to analyze and produce systematic knowledge about the practice capoeira Angola. The second objective sought to produce an analysis of this social practice based on their African cultural expressions in order to identify its potential as a collective praxis that can promote mental decolonization as well as personal and collective liberation. Therefore, I conducted a systematic study of fundamental references in African Psychology and made Doctorate Sandwich Program to deepen knowledge with most experienced researchers in the area in USA. I analyzed historical, political, philosophical and practical processes of Capoeira Angola within an African perspective, as well as the way they were experienced by two women, one white student and a black master teacher of Capoeira Angola. The first one is the researcher that assumed the dual role of researcher-participant, and the second is the participant who not only collaborated with her life story, but also contribution to the development of the investigation, assuming the dual role of participant-researcher. The analysis of the different dimensions described above was produced based on theoretical references of capoeiristas researchers, masters teachings transmitted orally, knowledge embodied in the body of the participants, dairy field of the visits to capoeira groups, in-depth conversations with the participant-researcher and the researcher-participant's self-interview. The research shows that the practice of capoeira Angola perpetuates linguistic, ritualistic, oral, musical and corporal knowledge from African ancestral cultures. These skills have multiple meanings and are articulated in a multifaceted way providing learning about life in their physical, mental and spiritual dimensions. The analysis of the participants experiences in the practice of capoeira Angola demonstrates that this culture has the potential to promote personal critical self-reflection in society from the opportunity to experience and embody new ways to see, think, feel and live in the world. This critical experience has created conditions for participants undertake personal and collective self-determination processes in society. They not only decolonized their lives but also they learned how to develop liberation community praxis in their personal relationships and professional work